Crystal-Chemical and Structural Characterization of Omphacite in High-Pressure Eclogites From the Arquía Complex on Southwestern Pijao, Central Cordillera (Colombian Andes) - Castellanos-Alarcón, Oscar Mauricio; Cedeño Villarreal, Karoll Michelle; Toro Hernández, Robert Antonio; Ríos-Reyes, Carlos Alberto; Henao-Martínez, José Antonio; Zuluaga-Castrillón, Carlos Augusto (Frontiers in Earth Science, 2022)
The Arquía Complex on southwestern Pijao, Central Cordillera (Colombia Andes) is a metamorphic unit made up of rocks with igneous and sedimentary protolith, metagabroid type, granatiferous amphibolites, amphibolic schists, sericitic quartz schists and medium to low pressure quartzites, as well as lawsonite and glaucophane schists, high pressure eclogites and serpentinized ultramafic rocks. Eclogites reveal PT conditions of metamorphism of 18-23 kbar and 620-670 °C, while the retrograde stage reached the epidote-amphibolite and greenschists facies with ranges between 9-14 kbar and 540-590 °C. High-pressure rocks of the Arquía Complex are considered to be the product of a tectonic melange exhumed through a fossil subduction channel, as a result of a converging process of a pacific accretionary subduction type, sutured in its current tectonic position within the Colombian Andes. The focus of this study is the crystal chemical and structural characterization of omphacite of eclogites of the Arquía Complex, which is well-preserved. Its show a chemically homogeneity in elemental composition and space group P2/n. Omphacite normally shows symplectitic intergrowths or a relictic character partially and totally included in amphibole. The reaction history can be synthesized in the decomposition of omphacite into symplectites as a product of decompression and hydration through the reaction: omphacite + quartz = plagioclase + clinopyroxene (low in Na), which can be considered a discontinuous precipitation reaction.